Knowledge of non-dental surgeon residents in a Multiprofessional Health Residence Program about early childhood caries and its prevention (Brazilian Journal of Health Research, 2021)
Introduction:Individuals participating in the daily routine of multiprofessional teams, should have basic knowledge about different Health fields to help reinforcing preventive guidelines and to be able to refer patients to different care services, whenever necessary. Objective: Investigating the knowledge of non-dental surgeon residents in a Multiprofessional Health Residence Program about the concept and prevention of dental caries in early childhood. Methods: Cross-sectional observational analytical study conducted with 47 residents graduated in Occupational Therapy, Psychology, Nutrition, Social Work, Pharmacy, Nursing, Speech Therapy and Physiotherapy, who were enrolled in the Multiprofessional Residency Program in Child and Adolescent Health (Federal University of Espírito Santo – Vitória City-ES) in 2016, 2017 and 2018. Six dental surgeons were excluded from the study. A self-administered questionnaire about oral health was applied to participants. Data were processed statistically through arithmetic mean and bivariate analyses (Chi-square and, Fisher tests, and Maximum Likelihood Ratio), at 5% significance level. Results: Most participants reported lack of approach to oral health during undergraduate course and presented satisfactory knowledge about prevention (97.9%), referral to pediatric dentists (97.9%), association between nighttime bottle and caries (89.4%), sugar and caries (100%), oral hygiene schedule (85.1%), and fluoridated toothpaste (89.4%). There was no difference in age, graduation year, and residency admission year (p
Keywords: Dental caries; Children; Health education